α- Tocopherol Protects Wister Rats from Oxidative Stress Induced by Chlorpyrifos and E.coli Infection - Charushila Jaiswal; Y Verma; A B Shrivastav (Current Research in Pharmaceutical Sciences, 2012)
72 male albino rats of the Wistar strain were randomly divided into 6 groups. Rats of control group I was fed with standard feed and water through out of experiment. Group II rats were treated with of E. coli (0.3 ml) by intra-peritoneal (I/P) inoculation, before 24 hrs of both sacrifices i.e.on 15th and 30th day of experiment. Group III was treated with chlorpyrifos reconstituted with 2 ml soya oil @10.6mg/kg b.wt. orally daily for 30 days. Group IV was treated with chlorpyrifos same as group III and I/P inoculation of E. coli (0.3 ml) was same as group II. Group V was treated with chlorpyrifos same as group III with α-tocopherol (VE) @150mg/kg b.wt. 30 minutes before the administration of CPF. Group VI was treated with chlorpyrifos same as group IV with Vitamin E @150mg/kg b.wt. 30 minutes before administration of CPF. This regimen was administered orally for the period of 30 days. At the time of sacrifice blood sample was collected i.e. on day 15th and 30th of the experiment. Oxidative stress was evaluated by measuring erythrocyte osmotic fragility test using different salt concentrations. The study showed that α-tocopherol protects erythrocyte osmotic fragility induced by repeated CPF exposure and E. coli infection in albino rats.